Pengembangan Civic Participation Siswa Oleh Guru Pendidikan Pancasila Di SMP Negeri 1 Jonggat - Riska Septi Aryani Aryani; Mohammad Ismail; Sawaludin sawaludin (LPD Universitas PGRI Pontianak, 2026)
This research aims to determine how teachers help students improve their civic participation in Pancasila Education at SMP Negeri 1 Jonggat, and to identify the challenges and ease faced by teachers. This research uses a qualitative method with a phenomenological research type. The research subjects are students at SMP Negeri 1 Jonggat, while the informants in this study are Pancasila Education teachers. Research data was collected thru observation, interviews, and documentation. Data presentation techniques included data reduction, data display, and drawing conclusions using data validity techniques such as source triangulation, data triangulation, and time triangulation to check data accuracy. Research shows that students' civic participation grows thru two types of activities: extracurricular and intracurricular. The teacher has tried to instill values such as democracy, responsibility, discipline, and caring for others thru various activities that directly involve the students. However, doing this still faces some problems such as students' lack of learning motivation, some students being passive in discussions, and a lack of facilities and infrastructure. The results of this study indicate that students' civic participation at SMP Negeri 1 Jonggat has increased thanks to the active role of Pancasila Education teachers, although different teaching methods, better technology utilization, and stronger motivation for students are still needed to fully achieve the goals of civic education. Keywords: Civic Participation, Pancasila Education, Teacher’s Role